Fuzzy Based Implementation of Multi - Keyword Ranked Search over Encrypted Cloud Data in Secure Cloud Environment (International Journal of Scientific Research and Management (IJSRM), 2017)
Cloud computing enables the paradigm of data outsourcing. However, to protect data privacy, sensitive cloud data have to be encrypted before outsourced to the commercial public cloud, which makes effective data utilization service is a challenging task. Even though searchable encryption techniques allow users to securely search over encrypted data through keywords, they support only Boolean search and are not yet sufficient to meet the effective data utilization need that is inherently demanded by large number of users and huge amount of data files in cloud. Hence it is necessary to allow multiple keywords in the search request and return documents in the order of their relevance to the keywords. The works on searchable encryption focused on single keyword search or Boolean keyword search and the result produced by them are rarely sorted. An effective method proposed for this challenging problem is privacy-preserving search over encrypted cloud data. This method establishes a set of strict privacy requirements for such a secure cloud data utilization system through MRSE. Among various multi-keyword semantics, this method chooses the efficient similarity measure of “coordinate matching”. Then according to Top K Query method the sorted results are produced. The privacy is preserved by the chunk of data stored in a various server’s. Then further improvisation is taken to introduce low overhead on computation and communication in future.